Protein O-GlcNAcylation Regulates Innate Immune Cell Function - Dong, Hong; Liu, Zihao; Wen, Haitao (Frontiers in Immunology, 2022)
Abstract Metabolite-mediated protein posttranslational modifications (PTM) represent highly evolutionarily conserved mechanisms by which metabolic networks participate in fine-tuning diverse cellular biological activities. Modification of proteins with the metabolite UDP-N-acetylglucosamine (UDP-GlcNAc), known as protein O-GlcNAcylation, is one well-defined form of PTM that is catalyzed by a single pair of enzymes, O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). Previous studies have discovered critical roles of protein O-GlcNAcylation in many fundamental biological activities via modifying numerous nuclear and cytoplasmic proteins. A common mechanism by which O-GlcNAc affects protein function is through the cross-regulation between protein O-GlcNAcylation and phosphorylation. This is of particular importance to innate immune cell functions due to the essential role of protein phosphorylation in regulating many aspects of innate immune signaling. Indeed, as an integral component of cellular metabolic network, profound alteration in protein O-GlcNAcylation has been documented following the activation of innate immune cells. Accumulating evidence suggests that O-GlcNAcylation of proteins involved in the NF-B pathway and other inflammation-associated signaling pathways plays an essential role in regulating the functionality of innate immune cells. Here, we summarize recent studies focusing on the role of protein O-GlcNAcylation in regulating the NF-B pathway, other innate immune signaling responses and its disease relevance.